Fertility, age, and the motherhood wage penalty in South Africa - Torrington, Catherine (School of Economics, 2023)
The difference in earnings between mothers and women without children is well-documented around the world. In developing countries, however, there has been far less research on the effect of fertility on wages for women. In this dissertation, I study the effects of fertility on wages for African women in South Africa. Using the National Income Dynamics Study (NIDS), I study the changes in wages experienced by mothers and non-mothers using panel data methods, as well as Ordinary Least Squares. I find that mothers in South Africa experience a small penalty, but this is not experienced equally for all mothers. Mothers with three or more children experience a greater penalty than mothers with fewer children, while the effects of having young children does not substantially affect the difference in earnings experienced by mothers. Since the majority of women in South Africa become mothers, a high proportion of the employed female population will experience a wage penalty in South Africa. Family- friendly policies, such as subsidized childcare, and flexible working options for mothers, would go a long way to reducing the wage penalty experienced by South African mothers.